Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1136/bmjopen-2021-049556
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative study of facilitators and barriers for continued follow-up care as perceived and experienced by young people with congenital heart disease in Sweden

Abstract: In-depth understanding of factors perceived by young people with congenital heart disease (CHD) to affect continued follow-up care is needed to tailor preventive strategies for discontinuation of follow-up care. To identify facilitating factors, low-prevalence settings in terms of discontinuation should be investigated.ObjectiveThis qualitative study describes factors affecting continued follow-up as perceived and experienced by young adults with CHD.ParticipantsUsing a mixed purposive sampling technique, 16 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Common experiences include extended wait times for medical appointments, increased responsibility for their medical care, and a general lack of continuity in connection to healthcare services 9,12 . Meeting adult healthcare services while feeling uneducated and unprepared can lead to a lack of follow‐up and loss of compliance 13 . Since AYAs in transition tend to be more vulnerable, 14 their health may be affected.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Common experiences include extended wait times for medical appointments, increased responsibility for their medical care, and a general lack of continuity in connection to healthcare services 9,12 . Meeting adult healthcare services while feeling uneducated and unprepared can lead to a lack of follow‐up and loss of compliance 13 . Since AYAs in transition tend to be more vulnerable, 14 their health may be affected.…”
Section: Introductionmentioning
confidence: 99%
“…It can include significant health risks. Previous studies have shown transfer to be linked with lack of treatment adherence, 13,22 and psychosocial burdens 4,23,24 that can affect the continuity of care 9 . Psychological distress from long‐term illness can also create a barrier to self‐management 23 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation